Microbial Nanotechnology for Bioremediation of Industrial Wastewater - Mandeep,; Shukla, Pratyoosh (Frontiers in Microbiology, 2020)
Pollutant removal from industrial effluents is a big challenge for industries. These pollutants pose a great risk to the environment. Nanotechnology can reduce the expenditure in industries to mitigate these pollutants through eco-friendly nanomaterials production. Nanomaterials are getting attention due to their enhanced physical, chemical, and mechanical properties. The production of nanoparticles with the help of microorganisms provides a greater boost to green biotechnology as an emerging field of nanotechnology for sustainable production and cost reduction. In this minireview, the efforts are made to discuss the various aspects of industrial effluent bioremediation through microbial nanotechnology integration. The use of enzymes with nanotechnology has provided higher activity and reusability of enzymes. This minireview also provides an insight into the advantages of the use of nanotechnology as compared to the conventional practices in these areas.